The expression of socio-emotional competence among younger Lithuanian adolescents as the precondition for their creativity - Butvilas, Tomas; Kovaitė, Kristina (Creativity Studies, 2022)
Socio-emotional education is sometimes referred to as the missing part that links academic knowledge to success in school, family, community, workplace, and life. Emotion intelligence is basically a construct that has gained rather great interest nowadays, especially its influence on interpersonal relationships by contributing to optimal social functioning. Recent events both in the country and in the world show how dangerous it is when children do not acquire a solid moral foundation in acquiring knowledge. Meanwhile, socio-emotional education linked to academic teaching helps to solve this issue. Recently, there has been more and more discussions about socio-emotional education and its positive impact on children’s psychological health. Socio-emotional abilities (so-called “emotional intelligence”, “social intelligence”) are the abilities to work together with others, to learn productively, to play the most important roles in the family, community, workplace. Success not only in school but also in later life phases accompanies those students who: a) realistically evaluates oneself and one’s possibilities (self-awareness); b) properly manages their feelings and controls their behavior (self-control); c) accurately interprets the signs of the social environment (social awareness); d) effectively resolves interpersonal conflicts (communication skills); e) makes good decisions in the face of day-to-day difficulties (responsible decision making). Therefore, this paper discusses on how to identify the knowledge and skills of students in socio-emotional education and at the same time to identify certain areas where some gaps still exist.